Alterations on high HbF levels may be associated with KLF1 gene mutations - Aydin, M.; Rencuzogullari, E.; Bayram, S.; Sevgiler, Y.; Genc, A. (Cellular and Molecular Biology, 2017)
The KLF1 gene synthesizes a transcription factor in the zinc finger structure that regulates the transcription of Î²-, Î³-globin, and Foxm1 genes. This factor plays an important role in the erythropoiesis mechanism by modifying the chromatin structure and is involved in the regulation of transcription in the opening of the Î²-globin gene. Î²-globin gene expression could be disrupted by a mutation, which may be a possible cause of a disruption in regulation of the promotor of the Î²-globin gene where the KLF1 transcription factor binds. This can lead to an inherited high fetal hemoglobin (HbF) ratio in people. Therefore, the main aim of this study was to determine the effects of KLF1 mutations on these high levels of HbF. In this study, in order to determine the relationship between the KLF1 mutations and the high HbF levels three exons along with the 5’-UTR and 3’-UTR regions of the KLF1 gene were sequenced of 53 volunteers. In this study, 3 variations in the non-coding regions of the KLF1 gene were not associated with a high level of HbF. Five variations were detected in the second exon of KLF1 gene. One of these is a frame shift that occurs when GG bases are inserted between the 59-60 codons, and the other four variations occur as a base substitution variations. No correlation was found between high HbF levels and neutral variants. Only polar-nonpolar amino acid changes were found at two points. At one of them, a significant drop in the high HbF levels was observed, while the other was observed to be high near to the critical limit. These findings suggested that variations in function of the KLF1 gene can alter the HbF levels.